Relationships between perception of illness, social support and hemodialysis adequacy - Sak, Jarosław; Dryl-Rydzyńska, Teresa; Książek, Andrzej (Polish Journal of Public Health, 2015)
Introduction. The patients in situations of “being ill” have to face not only pain and disabilities, but also problems in their social relationships. Perceptions of illness are results of reactions to the changes in the existential situations, and that these correspond to determined illness coping strategies.Aim. The aim of the research was to determine the relationships between perception of illness and social support, with the indicators of the adequacy of the renal replacement treatment and the level of urea as a biomarker of disease offset.Material and methods. The study was conducted on a group of 150 patients who were on chronic hemodialysis, and who were suffering from end stage renal disease. The patients were treated at on of the several Fresenius Medical centres. As a group, average Kt/V value was 1.45 (SD=0.22) and the URR ratio 71.78 (SD=5.95). Moreover, average urea concentration before HD equaled to 133.78mg% (SD=39.68) and after hemodialysis – 38.22mg% (SD=14.60). The research procedure was based on a questionnaire study. This applied three standardized scales: the Imagination and Perception of Illness Scale (IPIS), the brief Illness Perception Questionnaire (IPQ-Brief) and the Berlin Social Support Scale (BSSS).Results. Patients who exhibited higher values of urea concentration in the blood serum measured before HD, perceived their disease (IPIS scale) as causing more motivation loss to carrying out specific activities, as well as mental and physical sphere destruction, pessimism and lost control over the disease. What is more, higher values of urea reduction ratio (URR) positively correlate with the loss of control over the disease (r=-0.20, p=0.024). Moreover, patients characterized by higher values of urea concentration in the blood serum before hemodialysis, evinced greater need for social support (BSSS).Conclusions. The need for social support among ESRD patients treated by hemodialysis does not correlate with dialysis adequacy indicators. Furthermore, the level of urea marked before hemodialysis exhibits an interdependence with psychological determinants of illness perception and social support.